Authoritarian Leadership Style of Principals at the Elementary Education Level: A Review of the Literature - Muhammad Huda; Marevic Jean P. Lutog; Nerru Pranuta Murnaka (Kelola: Jurnal Manajemen Pendidikan, 2026)
This study aimed to examine authoritarian leadership styles at the elementary school level by highlighting their characteristics in elementary education. The problem this research addresses is the impact of authoritarian leadership implemented by school principals, particularly its strengths and weaknesses. This study used a qualitative approach and a literature review method, collecting literature from the Google Scholar database from 2019–2024 and from January to April 2025, using keywords related to authoritarian leadership in elementary schools. The literature was then filtered into 15 primary sources based on their relevance and focus on the research topic. The criteria for the literature used discuss authoritarian leadership in the context of elementary schools. The findings revealed that authoritarian leadership can improve discipline and rapid decision-making, but it often hinders creativity, collaboration, and a sense of togetherness among educators and leads to increased stress and decreased motivation. The conclusion of this study states that authoritarian leadership helps achieve school goals by maintaining teacher discipline, yet it negatively impacts teacher creativity, cooperation, and job satisfaction. Thus, school principals need to use this style selectively and responsibly, combining it with other leadership approaches that are more adaptive to the situation and the characteristics of team members.